An Investigation on Innovative Application in Hospitals Affiliated with Public Health Sector of Metropolitan City of Istanbul - Ekinci, Gülay; Bakır, İhsan; Ekinci, Gülay (Haşim Çapar, 2020)
Objective: With this study we aimed to investigate whether some variables (number of levels, departments, and horizontal communication etc.) in organizational structure of the hospitals operating within the frame of public health sector of the Metropolitan City of Istanbul have an impact on innovation, to determine the way these variables effect innovation, and evaluate innovative performance of our hospital within the frame of organizational innovative culture. Material and Method: For this investigation literature screening was made, and a questionnaire consisting of three parts was prepared. First part of the questionnaire contained institutional information, the second part comprised organizational information, and the third part consisted of questions aimed to determine the innovational value of the applications. The questionnaire forms were sent to 190 healthcare professionals. A total of 137 forms were completed by the participants, and returned to us. However only 112 questionnaire forms were taken into consideration for evaluation. The data obtained were analyzed using SPSS. Results: Hypothesis 1: Any correlation does not exist between the age of the hospital, and innovativeness (r=-0.276 p=0.004). Hypothesis 2: Any correlation does not exist between innovativeness, and formality in horizontal communication between hospital professionals of the same level (r=0.111 p=0.249 Kendall’s Tau_b=0.062). Hypothesis 3: A significant correlation does not exist between the communication between hospital employers, and their superiors, and innovativeness (r= 0,220 p=0.022). Hypothesis 4: A correlation does not exist between the horizontal communication prevalent among hospital employees at the same level, and innovativenes (r=0.159 p=0.099 Kendall’s Tau_b=0.145). Hypothesis 5: A difference does not exist between the general level of communication in the hospital, and innovativeness (r=0.305 p=0001). Hypothesis 6: A correlation does not exist between the number of departments in the hospital, and innovativeness (r=-0.141 p= 0.152 Kendall’s Tau_b=-0.119) Hypothesis 7: A correlation does not exist between the number of vertical levels in the hierarchy of hospital organization, and innovativeness (r=0117 p=0.234 Kendall’s Tau_b= 0.90). Conclusion: The outcomes of our study can be interpreted as follows: a) Newly established hospitals participating in our study were more innovative, b) Increased communicative relationship between employees, and their superiors, and also between workers at the same level, consequently among all hospital professionals reinforce innovativeness, c) as the number of departments increase, rapport, and communication weaken which decrease innovativeness, d) in hospitals with higher number of vertical levels, innovativeness is promoted in that the presence of more participative management, and effective communication channels facilitate implementation of innovative applications.

Amaç: Bu çalışma ile İstanbul ili sağlık sektöründe faaliyet gösteren hastanelerin örgüt yapısındaki bazı değişkenlerin (kademe sayısı, departman sayısı, yatay iletişim vb.) yenilikçiliği etkileyip etkilemediği; etkiliyorsa ne yönde etkilediğinin tespiti ile örgütsel yenilik kültürü çerçevesinde hastanemizin yenilik performansının değerlendirmesinin yapılması amaçlanmıştır. Gereç ve Yöntem: Araştırma için literatür taraması yapılmış ve üç bölümden oluşan anket hazırlanmıştır. Anketin birinci bölümünde kurumsal bilgiler; ikinci bölümde örgüt yapısına ait bilgiler, üçüncü bölümde hastanelerdeki uygulamaların ne kadar yenilikçi olduklarının tespitine ait sorular hazırlanmıştır. Anketler 190 sağlık çalışanına mail ortamında gönderilmiş ve 137 adet anketin geri dönüşü sağlanmış, ancak 112 adeti değerlendirmeye alınmıştır. Elde edilen veriler SPSS ile analiz edilmiştir. Bulgular: Hipotez 1: Hastanelerin yaşı ile yenilikçilik arasında ilişki yoktur (r=-0,276 p=0,004). Hipotez 2: Aynı seviye hastane çalışanlarının yatay ilişkilerindeki resmiyet ile yenilikçilik arasında ilişki yoktur (r=0,111 p=0,249 Kendall’s Tau_b=0,062). Hipotez 3: Hastanede çalışan astlar ve üstler arasındaki iletişim ile yenilikçilik arasında anlamlı bir ilişki yoktur(r= 0,220 p=0,022). Hipotez 4: Hastanede aynı seviyede çalışanlar arasındaki yatay iletişim ile yenilikçilik arasında ilişki yoktur (r=0,159 p=0,099 Kendall’s Tau_b=0,145). Hipotez 5: Hastane bütününde örgüt içi genel iletişim seviyesi ile yenilikçilik arasında fark yoktur (r=0,305 p=0,001). Hipotez 6: Hastanedeki departman sayısı ile yenilikçilik arasında ilişki yoktur (r=-0,141 p= 0,152 Kendall’s Tau_b=-0,119) Hipotez 7: Hastane organizasyonun hiyerarşisinde dikey kademe sayısı ile yenilikçilik arasında ilişki yoktur (r=0,117 p=0,234 Kendall’s Tau_b= 0,90) Sonuç: Çalışmamıza katılan hastanelerin daha genç olması sebebiyle daha yenilikçi olduğu, astlarla üstler arasında ve aynı seviye çalışanlar arasında ve hastane bütününde iletişimin artmasının yenilikçiliği artırdığı, departman sayısı arttıkça departmanlar arası ilişki ve iletişimin zayıflaması nedeniyle yenilikçiliğin azaldığı, dikey kademe sayısının yüksek olan hastanelerde yenilikçiliğin arttığı bu durumunda daha katılımcı bir yönetim ve etkin iletişim kanallarının varlığı nedeniyle yenilik uygulamalarını kolaylaştığı şeklinde yorumlanmıştır.
İstanbul İli Kamu Sağlık Sektöründe Faaliyet Gösteren Hastanelerde Yenilik Uygulamalarının Tespitine Yönelik Bir Araştırma
Bu makale “İstanbul İli Sağlık Sektöründe Faaliyet Gösteren Hastanelerde Yenilik (İnovasyon) Uygulamalarının Tespitine Yönelik Bir Araştırma” başlığı ile 6. Uluslararası Sağlık ve Hastane Yönetimi Kongresi’nde poster bildiri olarak sunulmuştur.
Keywords: Innovation; Organizational structure; Communication; Health; Hospital; İnovasyon; Örgüt yapısı; İletişim; Hastane; Sağlık